The influence of financial technology, financial literacy and financial attitudes on the financial behavior of micro, small and medium enterprises (MSMEs) - Rohi Bire, Amram; Maria, Maria; Manteiro, Maria C. B.; Hamu, Adriyana Lemba Ana (Institute of Computer Science (IOCS), 2023)
The aim of the research is to investigate the Influence of Financial Technology, Financial Literacy and Financial Attitudes on the Financial Behavior of Micro, Small and Medium Enterprises (MSMEs) Data Analysis techniques were carried out through Multiple Linear Regression Analysis with Multiple Linear Regression Formula Y=a+bX1+bX2+bX3+e. The results showed that there was a partial influence of financial technology on the financial behavior of Micro, Small and Medium Enterprises (MSMEs) owners receiving People's Business Credit (KUR) from PT. Bank Rakyat Indonesia, Kupang Branch while Financial Literacy Does Not Partially Affect the Financial Behavior of Micro, Small and Medium Enterprises (MSMEs) Owners Receiving People's Business Loans (KUR) from PT. Bank Rakyat Indonesia, Kupang Branch and also the variable Financial Attitude have no effect on Financial Attitude. However, simultaneously there is the influence of financial technology, financial literacy and financial attitudes on the financial behavior of Micro, Small and Medium Enterprises (MSMEs) owners receiving People's Business Credit (KUR) from PT. Bank Rakyat Indonesia, Kupang Branch amounted to 6.6% while 93.3% was influenced by other factors not examined in this study. With the Regression Equation obtained Y=21.426+0.401X1-0.248X2-0.105X3+e